Synthesis of Gold Nanoparticle Integrated Photo-responsive Liposomes and Measurement of Their Microbubble Cavitation upon Pulse Laser Excitation - Mathiyazhakan, Malathi (2016)
Photo-responsive nanoparticles (NPs) have received considerable attention because of their potential in providing spatial, temporal, and dosage control over the drug release. However, most of the relevant technologies are still in the development process and are unprocurable by clinics. Here, we describe a facile fabrication of these photo-responsive NPs with commercially available gold NPs and thermo-responsive liposomes Calcein is used as a model drug to evaluate the encapsulation efficiency and the release kinetic profile upon heat/light stimulation. Finally, we show that this photo-triggered release is due to the membrane disruption caused by microbubble cavitation, which can be measured with hydrophone.